Strongylids Profile on Horses in East Java - Puput, Sesa; Suwanti, Lucia Tri; Mufasirin, Mufasirin; Yunus, Muchammad; Suprihati, Endang; Aksono, Eduardus Bimo; Puspitasari, Heni (Jurnal Medik Veteriner, 2023)
Strongylids are a group of worms that infect the digestive tract of horses consisting of Strongylus vulgaris, Strongylus equinus, Strongylus edentates and Cyathostomes. There is no reported prevalence data on Strongylids infection in horses in East Java. Study on Strongylids is urgently needed because this worm is one of the causes of zoonotic diseases. This study aimed to identify Strongylids that infect horses morphologically. Identification of Strongylids in this study using morphological methods. A total of 65 horse faeces in East Java, i.e. in the cities of Surabaya, Malang, Kediri and Pasuruan were examined microscopically after being fixed in 10% formalin. Three microscopically positive samples showed a prevalence of 4,6% with an average size of 60-70µm x 50-60µm and larvae developed inside the worm eggs.